Cerebrovascular Dysfunction in Atrial Fibrillation - Junejo, Rehan T.; Lip, Gregory Y. H.; Fisher, James P. (Frontiers in Physiology, 2020)
It is now well established that besides being the most common sustained arrhythmia, atrial fibrillation (AF) is a major healthcare burden. Risk of debilitating stroke is increased in AF patients, but even in the absence of stroke, this population is at heightened risk of cognitive decline, depression, and dementia. The reasons for this are complex, multifactorial, and incompletely understood. One potential contributing mechanism is cerebrovascular dysfunction. Cerebral blood flow is regulated by chemical, metabolic, autoregulatory, neurogenic, and systemic factors. The dysfunction in one or more of these mechanisms may contribute to the elevated risk of cognitive decline and cerebrovascular events in AF. This short review presents the evidence for diminished cerebral blood flow, cerebrovascular carbon dioxide reactivity (i.e., cerebrovascular vasodilatory reserve), cerebral autoregulation, and neurovascular coupling in AF patients when compared to control participants in sinus rhythm. Further work is needed to understand the physiological mechanisms underpinning these observations and their clinical significance in atrial fibrillation patients.